Collaboration after Conflict: A Lesson from Collaborative Action in Customary Land Tenure Conflicts in Lombok, Indonesia - Aryogito Nindyatmoko; Kristina Setyowati; Rina Herlina Haryanti (Forestry Faculty, Universitas Hasanuddin, 2022)
Land tenure conflicts in Lombok occured due to social interactions between community and state institutions. These were triggered by the unilateral claims of some of the villagers of Bebidas who acted on behalf of indigenous communities to take back what they believed to be their ancestral land in the Mount Rinjani National Park area. This paper analyzes how stakeholders generated conflict resolution efforts that emphasized inclusive efforts by collaborative action through dialogue based on collaborative governance theory. Data were obtained from interviews with several key informants from various levels of government, as well as members of the Bebidas village community and NGO representatives. Documentation and observation were also carried out to obtain data validity over sustained data collection and analysis process. Findings show that conflict resolution resulted from a long-term process that built up from dialogues involving various stakeholders, which encouraged the emergence of Mutual Agreements and Memorandum of Understanding as milestones to end conflicts. This helped to initiate peaceful relations. Findings suggest that capacity building, promoting awareness, and technical training to support rights and livelihoods on an ongoing basis help to address conflicts rooted in knowledge imbalances. In addition, expanding conservation partnership through community empowerment and ecosystem restoration programs assist in maintaining resources and supporting economic benefits underpin ideals of sustainable longer term uses of the Rinjani.